EFFECTS OF LEGISLATION FOR GIFTED AND TALENTED EDUCATION: WHAT SCHOOL MANAGERS SAY - Santos, Rosimeire dos; Guenther, Zenita Cunha; Zaniolo, Leandro Osni [UNESP] (Unesp-faculdade Ciencias & Letras, 2016)
This article results from a master's research aiming to investigate effects of the Brazilian laws regulating Special Education in the public school system, focusing on the provisions for Gifted and Talented students. The subjects were school principals and managers from the Paranapanema valley region, who had participated in the Educators Training Program - Inclusive Education: a Right to Diversity, promoted by the Brazilian Ministry of Education - MEC. Results suggest that: a) present official instructions have not helped to identify and/or provide specific intervention for these students; b) there is noticeable difficulty within the school principals/managers in understanding both the given concepts and adopted terminology; the identification practices are entirely restricted to a fragmented view of the process. Conclusions point out the need for more consistent and effective teacher training to help them to capture signs of high ability in the classroom, to recognize different natural ability domains, and the value of scaling up official recommendations and measures to develop practices, disengaged from one single theoretical stream, as it is now.
Keywords: Educational policy; Giftedness; talent; Gifted education